Sleep Duration and BMI: A Study Among First-Year Students of a Malaysian Muslim Gifted and Talented Institution - Nur Fazidah Asmuje@Asmuzi; Muhammad Nashwan Mohd Nasarudin; Abdul Razzak Khan Rustum Ali Khan; Rahayu Ahmad; Nurdalila A’wani Abdul Aziz (Universiti Sains Islam Malaysia, 2025)
Malaysian Journal of Science Health & Technology, Volume 11 issue 1 Page (20–25)